Penerapan Model Problem Based Learning untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik Kelas X - Raden Ajeng Tri Wahyuning Tyas (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
The problem of this research describes the application of the Problem Based Learning Model to increase the interest and learning outcomes of class X students of Network Computer Engineering SMK Mahfilud Duror II. This study aims to increase the interest and learning outcomes of students. This Classroom Action Research takes place in three cycles during the odd semester of the 2020/2021 school year. Data collection obtained from the test and observation methods. Observations made include aspects of interest, affective, cognitive and psychomotor aspects. The results showed an increase in the interest and learning outcomes of students through the application of the Problem Based Learning model. In the aspect of interest, it appears that students focus their attention on the lesson, follow all learning stages well, participate actively in group discussion activities, want to ask questions and try to answer teacher questions and dare to present the results of the discussion to the class. Acquisition of the percentage of interest has increased by 16.96% from cycle I to II, and by 4.31% from cycle II to III. While the percentage increase for learning outcomes amounted to 20.92% from cycle I to II and 13.47% from cycle II to III. The application of the Problem-based Learning model has succeeded in increasing students' interest in automatic learning which will also improve student learning outcomes.